Entre la tradición épica y la historia: la conquista espartana de Mesenia - Fornis, César (2017)
La conquista de la vecina región de Mesenia, después de dos durísimas guerras, permitió a Esparta poner las bases de su hegemonía política y militar en la Hélade ya desde el Arcaísmo. En este trabajo se ofrece una reconstrucción del proceso de conquista y se analizan las fuertes tensiones que, como consecuencia del mismo, vivió la sociedad lacedemonia. Para ello se ha hecho uso del testimonio esencial, aunque fragmentario, del poeta contemporáneo Tirteo, de unas fuentes literarias tardías plagadas de elementos legendarios y sometidas al debate ideológico sobre la esclavización del pueblo mesenio y de la parca información aportada por la arqueología.
The two Messenian wars, culminating in the Spartan conquest of the fertile neighboring region of Messenia and the enslavement of its inhabitants, who became helots, remain largely unknown, mainly due to the lack of sources. Apart some verses of Tyrtaeus, the Spartan poet of the mid-seventh century BC, the literary sources are belated and gather suspicious and contaminated ancient traditions riddled with legendary elements and subjected to the ideological debate about the enslavement of Greek people (and as Dorian as their Spartan conquerors). This has caused sharp controversies in modern historiography, which affect both the chronology and the credibility (and even the historicity) of certain episodes. According to an hypercritical posture, the possibility of reaching a minimum reconstruction and understanding of the historical events has even been denied, in such a way that the need to obviate them has been postulated. From our point of view, the historian himself/herself can (and should) perform this task of analysis and interpretation, but while taking extreme caution with these sources and, whenever possible, approaching the data provided by Archaeology; it is also essential to insert the two Messenian wars in structural problems and developments of the early Archaic Age, and not to isolate them, as has often been done. In this way, the conquest of Messenia emerges as an enterprise undertaken by the recently unified Lacedaemonian state as part of its process of territorial, identity and ideological definition. With the completion of the conquest, Sparta reaches the recognition as a model state for Greek political theorists because there is full identification between the political and military body, that is, between citizens and hoplites, who can devote themselves to the work deemed worthy (the management of public affairs and war) thanks to the existence of dependent masses who work the land owned by their masters.
Keywords: Tirteo; Poesía épica; Esparta (Ciudad desaparecida)